Comparison of Bacterial Microbiota in Raw Mare’s Milk and Koumiss Using PacBio Single Molecule Real-Time Sequencing Technology - Zhang, Meng; Dang, Na; Ren, Dongyan; Zhao, Feiyan; Lv, Ruirui; Ma, Teng; Bao, Qiuhua; Menghe, Bilige; Liu, Wenjun (Frontiers in Microbiology, 2020)
Koumiss is a traditional fermented raw mare’s milk product. It contains high nutritional value and is well-known for its health-promoting effect as an alimentary supplement. This study aimed to investigate the bacterial diversity, especially lactic acid bacteria (LAB), in koumiss and raw mare’s milk. Forty-two samples, including koumiss and raw mare’s milk, were collected from the pastoral area in Yili, Kazakh Autonomous Prefecture, Xinjiang Uygur Autonomous Region in China. This work applied PacBio single-molecule real-time (SMRT) sequencing to profile full-length 16S rRNA genes, which was a powerful technology enabling bacterial taxonomic assignment to the species precision. The SMRT sequencing identified 12 phyla, 124 genera, and 227 species across 29 koumiss samples. Eighteen phyla, 286 genera, and 491 species were found across 13 raw mare’s milk samples. The bacterial microbiota diversity of the raw mare’s milk was more complex and diverse than the koumiss. Raw mare’s milk was rich in LAB, such as Lactobacillus (L.) helveticus, L. plantarum, Lactococcus (Lc.) lactis, and L. kefiranofaciens. In addition, raw mare’s milk also contained sequences representing pathogenic bacteria, such as Staphylococcus succinus, Acinetobacter lwoffii, Klebsiella (K.) oxytoca, and K. pneumoniae. The koumiss microbiota mainly comprised LAB, and sequences representing pathogenic bacteria were not detected. Meanwhile, the koumiss was enriched with secondary metabolic pathways that were potentially beneficial for health. Using a Random Forest model, the two kinds of samples could be distinguished with a high accuracy 95.2% (Area under the curve, AUC=0.98) based on 42 species and functions. Comprehensive depiction of the microbiota in raw mare’s milk and koumiss might help elucidate evolutionary and functional relationships among the bacterial communities in these dairy products. The current work suffered from the limitation of a low sample size, so further work would be required to verify our findings.